Agouti and BMP signaling drive a naturally occurring fate conversion of melanophores to leucophores in zebrafish - Delai Huang; Emaan H. Kapadia; Yipeng Liang; Leah P. Shriver; Shengkun Dai; Gary J. Patti; Bruno M. Humbel; Vincent Laudet; David M. Parichy (Proceedings of the National Academy of Sciences, 2025)
The often-distinctive pigment patterns of vertebrates are varied in form and function and depend on several types of pigment cells derived from embryonic neural crest or latent stem cells of neural crest origin. These cells and the patterns they produce have been useful for uncovering features of differentiation and morphogenesis that underlie adult phenotypes, and they offer opportunities to discover how patterns and the cell types themselves have diversified. In zebrafish, a body pattern of stripes arises by self-organizing interactions among three types of pigment cells. Yet these fish also exhibit white ornamentation on their fins that depends on the transdifferentiation of black melanophores to white cells, “melanoleucophores.” To identify mechanisms underlying this conversion we used ultrastructural, transcriptomic, mutational, and other approaches. We show that melanophore–melanoleucophore transition depends on regional BMP signals transduced through noncanonical receptors (Rgmb-Neo1a-Lrig2) as well as BMP-dependent signaling by Agouti genes, asip1 and asip2b . These signals lead to expression of transcription factor genes including foxd3 and runx3 that are necessary to induce loss of melanin, curtail new melanin production, and deploy a pathway for accumulating guanine crystals that, together, confer a white phenotype. These analyses uncover an important role for positional information in specifying ornamentation in zebrafish and show how tissue environmental cues and an altered gene regulatory program have allowed terminal addition of a distinct phenotype to a preexisting cell type.